Donor‐specific antibodies are associated with micro‐ and macrovascular coronary disease, restrictive myocardial damage, and poor outcome in heart‐transplanted patients. Issue 9 (11th July 2017) - Clemmensen, Tor Skibsted; Koefoed‐Nielsen, Pernille; Jensen, Lis‐Ann; Poulsen, Steen Hvitfeldt; Holm, Niels Ramsing; Løgstrup, Brian Bridal; Christiansen, Evald Høj; Dijkstra, Jouke; Valen, Kamilla Pernille Bjerre; Eiskjær, Hans
Abstract: Aims: We examined the relationship between donor‐specific HLA antibody (DSA) presence and graft function, hemodynamics, cardiac allograft vasculopathy (CAV), and major adverse cardiac events (MACE) in stable long‐term heart‐transplanted (HTx) patients. Methods: Sera from 79 patients (median 7.5 years after HTx) were analyzed for DSA presence. Graft function was evaluated by echocardiography and right heart catheterization. CAV burden was determined by coronary angiography, optical coherence tomography (OCT), and coronary flow velocity reserve (CFVR). Patients were prospectively followed after DSA assessment. MACE included significant CAV progression, heart failure, treated rejection, and cardiovascular death. Results: Sixty patients had no DSA, and 19 patients were sensitized. The vasculopathy burden by angiography, OCT, and CFVR was more pronounced in DSA‐positive patients than in DSA‐negative patients. DSA‐positive patients had higher pulmonary capillary wedge pressure (16 [8; 21] vs 9 mm Hg [7; 11], P <.05) and right atrial pressure (8 [6; 9] vs 4 mm Hg [2; 6], P <.01) and lower global longitudinal strain (−13% [−10; −15] vs −16% [−14; −17], P <.01) than DSA‐negative patients. DSA presence was a strong MACE predictor (HR 4.7 (95% CI 2.0‐11.4), P <.001). Conclusions: DSA‐positive patients had higher vasculopathy burden, higher filling pressures, and lower longitudinal myocardial deformation than DSA‐negative patients. The DSA presence was a strong MACE predictor.